Africa's Pulse, No. 22, October 2020 : An Analysis of Issues Shaping Africa’s Economic Future - Zeufack, Albert G.; Calderon, Cesar; Kambou, Gerard; Kubota, Megumi; Cantu Canales, Catalina; Korman, Vijdan (World Bank, Washington, DC, 2020)
COVID-19 has taken a large toll on economic activity in Sub-Saharan Africa, putting a decade of hard-won economic progress at risk. The pandemic is pushing the region into its first recession in 25 years. In 2020, GDP per capita is expected to contract by 6.5 percent in Sub-Saharan Africa and by the end of 2021, it’s likely to have regressed back to its 2007’s level. As a consequence, COVID-19 could push up to 43 million people into extreme poverty in Africa, erasing at least five years of progress in fighting poverty. The road to recovery will be long, steep, and must be paved with sound economic policies. Countries need to reconstitute fiscal space to help finance programs that can stimulate recovery. Better debt transparency and management, better service delivery, civil society engagement and less corruption will be critical. Ultimately, sustained recovery will depend on how fast African countries prioritize policy actions and investment that address the challenge of creating more, better and inclusive jobs. These policy priorities, in turn, operate through three critical (an inter-related) channels: the digital transformation, the sectoral reallocation, and the the spatial integration. Countries must expand digital infrastructure and make connectivity affordable, reliable and universal across Africa. Shifting resources towards non-traditional economic sectors with higher productivity, lower volatility and greater value addition, fully leveraging the African Continental Free Trade Area (AfCFTA) will be equally critical. Finally, fostering the reallocation of resources from less to more efficient job-creating locations through enhanced rural-urban, inland-coastal connectivity will be key to jobs and economic transformation. Interestingly, number of countries, especially in the East African Community and in the West African Monetary Union are seizing the opportunity of the crisis to accelerate these reforms.